2009
DOI: 10.1152/japplphysiol.91324.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue impairs physical performance in humans

Abstract: Mental fatigue is a psychobiological state caused by prolonged periods of demanding cognitive activity. Although the impact of mental fatigue on cognitive and skilled performance is well known, its effect on physical performance has not been thoroughly investigated. In this randomized crossover study, 16 subjects cycled to exhaustion at 80% of their peak power output after 90 min of a demanding cognitive task (mental fatigue) or 90 min of watching emotionally neutral documentaries (control). After experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

68
953
17
46

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,042 publications
(1,135 citation statements)
references
References 74 publications
68
953
17
46
Order By: Relevance
“…Related to perception of effort, but as yet unexplored sufficiently in the cognitive strategy-strength performance research is the role of mental fatigue, defined by Marcora and colleagues [46] (p. 857) as "a psychobiological state caused by prolonged periods of demanding cognitive activity and characterized by subjective feelings of "tiredness" and "lack of energy." Marcora and colleagues [46] revealed that mental fatigue limited performance in a cycling endurance task of 90 minutes through higher perception of effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to perception of effort, but as yet unexplored sufficiently in the cognitive strategy-strength performance research is the role of mental fatigue, defined by Marcora and colleagues [46] (p. 857) as "a psychobiological state caused by prolonged periods of demanding cognitive activity and characterized by subjective feelings of "tiredness" and "lack of energy." Marcora and colleagues [46] revealed that mental fatigue limited performance in a cycling endurance task of 90 minutes through higher perception of effort.…”
Section: Discussionmentioning
confidence: 99%
“…Marcora and colleagues [46] revealed that mental fatigue limited performance in a cycling endurance task of 90 minutes through higher perception of effort.…”
Section: Discussionmentioning
confidence: 99%
“…A soccer match involves mental activities for both goalkeepers and outfield players [139], and mental fatigue has been shown to impact cognitive and physical performance [140,141]. Neurocognitive mechanisms underlying the effects of mental fatigue are still poorly understood, although scientific evidence pointed out that mental fatigue is associated with lower cognitive performance and inadequate performance adjustments after errors [142].…”
Section: Cognitive Markersmentioning
confidence: 99%
“…These are the people for whom even the moderate effort required by physical activities like walking is too much. Importantly, there are common conditions like obesity [23] and mental fatigue [24] that exacerbate perception of effort during exercise. Therefore, a psychoactive drug that reduces perception of effort during exercise may be particularly useful for the many people who are overweight and/or exercise after work in a state of mental fatigue.…”
Section: Caffeine and Other Psychoactive Drugsmentioning
confidence: 99%